Analisis Persepsi Guru IPA atas Dukungan Manajemen Sekolah dan Ketersediaan Sumber Daya dalam Implementasi Kurikulum Internasional Berbasis Pembelajaran Mendalam - Siallagan, Dony Kurniawan; Musliman, Acep; Soenarno, Sri Murni (ALFARISI: Jurnal Pendidikan MIPA, 2026)
This qualitative study with a phenomenological approach examines the perceptions of Science teachers regarding school management support and resource availability in the implementation of international curricula (Cambridge, IB, IPC) based on deep learning in Jakarta. Through in-depth interviews with eight teachers and thematic analysis assisted by NVivo 15, this study aims to understand the construction of teacher perceptions and their impact on motivation, pedagogical strategies, and professional agency. The findings reveal an implementation paradox; on one hand, teachers perceive the availability of physical resources and professional development support as adequate, yet on the other hand, they face systemic barriers in the form of non-pedagogical workload, rigid bureaucratic procedures, and misalignment of resources with specific pedagogical needs, such as the lack of a school garden and unstable internet connectivity. This dialectical construction of perception encourages teachers to develop agency through creative adaptation strategies, such as informal collaboration, resource improvisation, and content modification, so that deep learning can still be realized. The implications of the research affirm the need for a paradigm shift in school support from a bureaucratic-administrative model towards a responsive ecological model, concluding that the success of international curricula is not linear with the completeness of resources, but is highly moderated by the quality of the supporting ecosystem and the empowerment of teacher agency.
Keywords: Agensi Guru; Pembelajaran Mendalam; Dukungan Manajemen; Kurikulum Internasional; Persepsi Guru